Analisis Persediaan Bahan Baku Multi Item Usaha Kerupuk Kulit Alhamdulillah Menggunakan Metode Economic Order Quantity - Cahyani, Vebby Afifah Cahyani; Rizal, Yusmet (UNIB Press, 2023)
Controlling raw material stocks is a crucial aspect of effective inventory management for businesses. The company's objective is to maximise profits. To maximise earnings, the corporation must prudently maintain appropriate inventory levels in order to limit existing inventory expenses. Kerupuk Kulit Alhamdulillah is a small to medium-sized business in the food industry that manufactures skin crackers in various packaging sizes. This is an example of applied research. This study employs the Lilliefors normality test to assess if the data are normally distributed. According to the findings of calculations using the method Economic Order Quantity (EOQ), the entire cost of multi-item raw material inventory according to the Kerupuk Kulit Alhamdulillah is Rp 4,703,520.00, however according to the EOQ method, the total cost is Rp 2,093.00. Kerupuk Kulit Alhamdulillah Business can save Rp 2,694,427.00 by utilising the EOQ approach.